Optimal duration of antibiotic treatment for community-acquired pneumonia in adults: a systematic review and duration-effect meta-analysis - Toshi A Furukawa; Yuki Kataoka; Yan Luo; Akira Onishi; Edoardo Ostinelli; Tasnim Hamza; Yuki Furukawa; Satoshi Funada (BMJ Open, 2023)
Objectives To find the optimal treatment duration with antibiotics for community-acquired pneumonia (CAP) in adults.Design Systematic review and duration-effect meta-analysis.Data sources MEDLINE, Embase and CENTRAL through 25 August 2021.Eligibility criteria All randomised controlled trials comparing the same antibiotics used at the same daily dosage but for different durations for CAP in adults. Both outpatients and inpatients were included but not those admitted to intensive care units. We imposed no date, language or publication status restriction.Data extraction and synthesis Data extraction by two independent reviewers. We conducted a random-effects, one-stage duration-effect meta-analysis with restricted cubic splines. We tested the non-inferiority with the prespecified non-inferiority margin of 10% examined against 10 days . The primary outcome was clinical improvement on day 15 (range 7–45 days). Secondary outcomes: all-cause mortality, serious adverse events and clinical improvement on day 30 (15–60 days).Results We included nine trials (2399 patients with a mean (SD) age of 61.2 (22.1); 39% women). The duration-effect curve was monotonic with longer duration leading to a lower probability of improvement, and shorter treatment duration (3–9 days) was likely to be non-inferior to 10-day treatment. Harmful outcome curves indicated no association. The weighted average percentage of the primary outcome in the 10-day treatment arms was 68%. Using that average, the absolute clinical improvement rates of the following durations were: 3-day treatment 75% (95% CI: 68% to 81%), 5-day treatment 72% (95% CI: 66% to 78%) and 7-day treatment 69% (95% CI: 61% to 76%).Conclusions Shorter treatment duration (3–5 days) probably offers the optimal balance between efficacy and treatment burden for treating CAP in adults if they achieved clinical stability. However, the small number of included studies and the overall moderate-to-high risk of bias may compromise the certainty of the results. Further research on the shorter duration range is required.PROSPERO registration number CRD 42021273357.